2019
DOI: 10.12659/msm.914318
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cold-Inducible RNA-Binding Protein Predicts Lung Dysfunction After Cardiovascular Surgery Following Cardiopulmonary Bypass: A Prospective Observational Study

Abstract: Background Cold-inducible RNA-binding protein (CIRP) has been identified as an inflammatory mediator that exerts its function in inflammatory diseases. However, the roles of CIRP in patients who received cardiovascular surgery necessitating cardiopulmonary bypass (CPB) are still unknown. The aim of this study was to examine CIRP levels and attempt to evaluate whether CIRP could serve as a predictor for lung dysfunction after cardiovascular surgery. Material/Methods Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The elevated levels of CIRP were correlated with the levels of inflammatory cytokines IL‐6 and IL‐10 37 . Furthermore, the length of CPB time was associated with the level of CIRP production, while CIRP level was correlated with the severity of lung dysfunction 37 . In brief, these results suggest that plasma CIRP could serve as a predictor for lung injury after cardiovascular surgery with CPB.…”
Section: Cirp As a Biomarker For Predicting Lung Dysfunction In Patie...mentioning
confidence: 72%
See 1 more Smart Citation
“…The elevated levels of CIRP were correlated with the levels of inflammatory cytokines IL‐6 and IL‐10 37 . Furthermore, the length of CPB time was associated with the level of CIRP production, while CIRP level was correlated with the severity of lung dysfunction 37 . In brief, these results suggest that plasma CIRP could serve as a predictor for lung injury after cardiovascular surgery with CPB.…”
Section: Cirp As a Biomarker For Predicting Lung Dysfunction In Patie...mentioning
confidence: 72%
“…The lung is among the most vulnerable organs during the perioperative period of cardiovascular surgery with CPB, and 20% of patients who received cardiovascular surgery had ALI during the perioperative period, with a mortality as high as 80%. Recently, the level of plasma CIRP was demonstrated to be a biomarker for predicting lung dysfunction in patients receiving cardiovascular surgery necessitating CPB 37 . In this study, plasma was collected at different time points during the perioperative period of the cardiovascular surgery with CPB and was then detected for the level of CIRP and inflammatory cytokines, coupled with the collection of other laboratory and clinical parameters at the time 37 .…”
Section: Cirp As a Biomarker For Predicting Lung Dysfunction In Patie...mentioning
confidence: 99%
“…Cen et al 28 demonstrated that CIRP deficiency can attenuate inflammation and oxidative stress and reduce renal injury after renal ischemia-reperfusion. Chen et al 29 found that the expression of CIRP in serum increased rapidly after CPB, then decreased gradually, and approached the preoperative level at 5 days after CPB. CIRP level could serve as a biomarker to predict the lung injury induced by cardiovascular surgery.…”
Section: Discussionmentioning
confidence: 98%
“…[21,22] In adult human patients, elevated plasma levels of eCIRP have been correlated with a poor prognosis in patients with sepsis and with lung dysfunction after cardiac surgery. [19,23,24] However, to our knowledge, eCIRP levels have never been assessed in neonates. Furthermore, the impact of eCIRP on cardiac tissue or cardiac function has never been studied.…”
Section: Introductionmentioning
confidence: 99%